Entrepreneurial behaviour of dairy farm women in Nainital district of Uttarakhand - Kholiya, Monika; Bhardwaj, Neelam (Indian Journal of Dairy Science, 2020)
The investigation was conducted in Nainital district of Uttarakhand to know the entrepreneurial behaviour of dairy farm women. A sample of total 120 respondents was selected from the five selected villages and pre-tested interview schedule was used for the data collection. Statistical techniques such as frequency, percentage, arithmetic mean, standard deviation, coefficient of correlation and t-test were used to analyze the data. The findings of the study revealed that majority of the respondents (72.5%) belonged to middle age category, 30.83 per cent had education up to high school, 69.17 per cent had medium family size, 59.16 per cent had medium dairy experience, 52.5 per cent respondents had medium herd size and milk production, 72.50 per cent had medium level of monthly income from dairy farming, 37.5 per cent had small land holding (1-2 hectares), 75 per cent had medium economic motivation and 77.5 per cent had medium scientific orientation. The study revealed that majority of the respondents (62.5%) had medium level of entrepreneurial behaviour with medium innovativeness (46.67%), achievement motivation (57.5%), decision making ability (70%), risk orientation (50%), coordinating ability (67.5%), planning ability (59.17%), information seeking behaviour (73.33%), cosmopoliteness (82.5%) and self-confidence (56.67%). It could be observed that family size, herd size, milk production, monthly income from dairy farming, land holding, economic motivation and scientific orientation showed positive and significant relationship with entrepreneurial behaviour at 1% level of significance, whereas education and dairy experience were positively and significantly related to entrepreneurial behaviour at 5% level of significance. On the other hand, age had positive and non-significant relationship with entrepreneurial behaviour of dairy farm women.